The crystalline sponge method updated - Hoshino, Manabu; Khutia, Anupam; Xing, Hongzhu; Inokuma, Yasuhide; Fujita, Makoto (IUCrJ, 2016)
Crystalline sponges are porous metal complexes that can absorb and orient common organic molecules in their pores and make them observable by conventional X-ray structure analysis (crystalline sponge method). In this study, all of the steps in the crystalline sponge method, including sponge crystal preparation, pore–solvent exchange, guest soaking, data collection and crystallographic analysis, are carefully examined and thoroughly optimized to provide reliable and meaningful chemical information as chemical crystallography. Major improvements in the method have been made in the guest-soaking and data-collection steps. In the soaking step, obtaining a high site occupancy of the guest is particularly important, and dominant parameters for guest soaking ( e.g. temperature, time, concentration, solvents) therefore have to be optimized for every sample compound. When standard conditions do not work, a high-throughput method is useful for efficiently optimizing the soaking conditions. The X-ray experiments are also carefully re-examined. Significant improvement of the guest data quality is achieved by complete data collection at high angle regions. The appropriate disorder treatment of the most flexible ZnI 2 portions of the host framework and refinement of the solvents filling the remaining void are also particularly important for obtaining better data quality. A benchmark test for the crystalline sponge method toward an achiral molecule is proposed with a guaiazulene guest, in which the guest structure (with ∼ 100% site occupancy) is refined without applying any restraints or constraints. The obtained data quality with R int = 0.0279 and R 1 = 0.0379 is comparable with that of current conventional crystallographic analysis for small molecules. Another benchmark test for this method toward a chiral molecule is also proposed with a santonin guest. The crystallographic data obtained [ R int = 0.0421, R 1 = 0.0312, Flack (Parsons) = −0.0071 (11)] represents the potential ability of this method for reliable absolute structure determination.